Next-Generation hyperpolarization techniques for NMR: amplifying signal sensitivity and resolving complex molecular systems - Schmidt Laustsen Vorm; Rößler Rößler; Pajvani Duckett (Institute of Computer Science (IOCS), 2022)
Nuclear Magnetic Resonance (NMR) spectroscopy is a powerful analytical tool used to investigate the structure and dynamics of molecules at the atomic level. However, its application to complex molecular systems, such as large biomolecules and diluted chemical mixtures, is often hindered by limited NMR signal sensitivity. To address this challenge, next-generation hyperpolarization techniques have emerged, offering the potential to enhance NMR signals significantly. This research explores the dynamic hyperpolarization enhancement process for NMR sensitivity through a mathematical formulation and a numerical example. The proposed model describes the transfer of polarization from polarizing agents to target molecules and its impact on nuclear spin polarization. The numerical example demonstrates how hyperpolarization techniques can amplify nuclear spin polarization over time, leading to improved NMR signal sensitivity. The research highlights the optimization of key parameters, such as relaxation time constants and polarization transfer rates, for achieving maximum sensitivity enhancements. The results underscore the transformative potential of hyperpolarization techniques in expanding the scope of NMR applications, enabling the study of complex molecular systems with unparalleled precision, and advancing scientific discoveries in biochemistry, materials science, and medical research. The conclusion emphasizes the ongoing efforts to develop next-generation hyperpolarization methods and their implications for fundamental and applied research. Ultimately, this research opens new frontiers in NMR spectroscopy, providing researchers with a powerful tool to explore intricate molecular systems and resolve scientific challenges across diverse disciplines